2001
DOI: 10.1128/aac.45.12.3631-3634.2001
|View full text |Cite
|
Sign up to set email alerts
|

Postantibiotic Effects of Antituberculosis Agents Alone and in Combination

Abstract: The postantibiotic effects (PAEs) of seven antimycobacterial agents, tested at their respective peak concentrations in serum alone and in different combinations, against Mycobacterium tuberculosis ATCC 27294 were studied with a radiometric culture system in parallel with the viable count method. Rifampin gave the longest PAE (67.8 h) among the drugs used alone, and combinations of first-line drugs generally gave PAEs longer than 120 h. The data obtained might help provide a better understanding of the scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 22 publications
5
25
0
Order By: Relevance
“…In the past, other researchers have demonstrated that rifampin indeed has a long PAE. Chan et al exposed M. tuberculosis to a rifampin C max /MIC of 32 and demonstrated a PAE of 2.8 days (5). This harmonizes well with our own result, in which a C max /MIC of 64.1 (approximately double the value of 32) had a PAE double the one demonstrated by Chan et al (5).…”
Section: Discussionsupporting
confidence: 80%
“…In the past, other researchers have demonstrated that rifampin indeed has a long PAE. Chan et al exposed M. tuberculosis to a rifampin C max /MIC of 32 and demonstrated a PAE of 2.8 days (5). This harmonizes well with our own result, in which a C max /MIC of 64.1 (approximately double the value of 32) had a PAE double the one demonstrated by Chan et al (5).…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, the PAE at 20 mg/liter of the drug appeared longer than that at 10 mg/liter, perhaps reflecting concentration dependence. The PAEs of rifapentine at therapeutic concentrations thus appear (at least) equivalent and might even be superior to those of rifampin (6). Isoniazid only produced a detectable PAE (Ͻ24 h), which corroborated the result of our previous study (6).…”
supporting
confidence: 80%
“…The PAEs of rifapentine at therapeutic concentrations thus appear (at least) equivalent and might even be superior to those of rifampin (6). Isoniazid only produced a detectable PAE (Ͻ24 h), which corroborated the result of our previous study (6). Moxifloxacin was found to have insignificant PAE at the concentration of 1 and 2 mg/liter.…”
supporting
confidence: 79%
See 2 more Smart Citations